Synthesis of database “Specialized computer networks” for the objects of oil and gas complex - Бабчук, Сергій Миронович (Eastern-European Journal of Enterprise Technologies, 2014)
In today’s world there are over a hundred different specialized computer networks. Detailed information about them in media is virtually absent. Nowadays, information about specialized computer networks is not generalized and structured. When upgrading, enterprises need to choose effective solutions for particular process sections. However, there is no methodological framework for effective solution of this problem. The structure of the knowledge base “specialized computer networks” and its mathematical model is given. The basic characteristics and features of specialized digital networks INTERBUS, CAN, CAN Kingdom, PROFIBUS-PA, Foundation Fieldbus H1 are presented in the paper. The developed knowledge base facilitates the structured formation of information about specialized computer networks. Also, it enables enterprise automation experts to select an optimal specialized computer network for a particular control object.